Implementasi Program Peremajaan Sawit Rakyat (PSR) dalam Perspektif Maqashid Syariah: Studi di Kabupaten Aceh Barat - Putra, Hendra; Lutfi , Anas; Sadino, Sadino (STAINI Press, 2025)
The People's Oil Palm Replanting Program (PSR) is a strategic policy of the government to increase the productivity and welfare of oil palm farmers. However, in its implementation, a number of violations of the law were found such as manipulation of data on program participants. This paper aims to review the implementation of the PSR program in West Aceh Regency from the perspective of Islamic law. Using a normative-empirical approach, this study refers to the principles of maqāṣid al-sharīʿah and fiqh siyasah in examining the role of the state in the distribution of justice, the validity of land ownership, and administrative violations. The results show that the PSR program is in accordance with the objectives of Islamic law, especially in the aspects of property protection (ḥifẓ al-māl) and community welfare (taḥqīq al-maṣlaḥah), but there is a need for improved governance to be in accordance with the principles of justice, transparency, and accountability as taught in Islamic law.